(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The Right to Education (RTE) is an act of Parliament of India enacted on 4 August 2009, which describes the modalities of the importance of free and compulsory education for children between ages 6-14 year in India under Article 21 A of the Indian constitution. India becomes one of 135 countries to make education a fundamental right of every child when act came into force on April 1, 2010. The right of children to free and compulsory education means that every child has a right to full time elementary education of satisfactory and equitable quality in a formal school which satisfices certain essential norms and standards.